2011
DOI: 10.2174/157016211795945250
|View full text |Cite
|
Sign up to set email alerts
|

Drug Resistance Mutations During Structured Interruptions of HAART in HIV-1 Infected Children

Abstract: Information concerning structured treatment interruptions (STI) of the Highly Active Antiretroviral Therapy (HAART) and their risk for selecting antiretroviral drug resistance in children is scarce. In this study, we searched for antiretroviral drug resistance mutations at the end of five viral rebounds of two children with HIV and a chronically undetectable viral load (VL) who underwent an STI program. The HAART was interrupted for 4 weeks and then restarted and continued for 12 weeks for three cycles. VL, CD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Instead, mutations detected in the protease may have been present before the STI scheme was initiated although it is hard to make correct interpretations of the data without a baseline sequence prior to the STI program. These mutations were also found in the previous study using standard genotyping to assess the effect of the STI [ 6 ]. Additionally, another study also reported the presence of these changes in naïve patients [ 24 ].…”
Section: Discussionsupporting
confidence: 61%
See 3 more Smart Citations
“…Instead, mutations detected in the protease may have been present before the STI scheme was initiated although it is hard to make correct interpretations of the data without a baseline sequence prior to the STI program. These mutations were also found in the previous study using standard genotyping to assess the effect of the STI [ 6 ]. Additionally, another study also reported the presence of these changes in naïve patients [ 24 ].…”
Section: Discussionsupporting
confidence: 61%
“…In all four patients, progressively lower viral rebounds were observed with a vigorous development of T CD8+ cells and an initial decrease in the response of T-helper cells, followed by a subsequent increase. In a second study, using a standard genotyping analysis and the HIVdb [ 12 ], the sequences codifying for the protease and reverse transcriptase were analyzed in samples corresponding to the viral rebounds of the STI program, finding no resistance to any of the PI or reverse transcriptase inhibitors commercially available [ 6 ]. Despite the limitations of the number of patients analyzed, the results of that previous work suggested that STI, in the context evaluated, could be safe; however, before suggesting new research in different populations of children, it is necessary to consider the genetic heterogeneity of the viral subpopulations during HIV infection and to assess the presence or absence of mutations associated with antiretroviral resistance even in minority viral populations infecting a patient.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although in most cases, the antibody-antigen enzymelinked immunosorbent assay test, HIV-1 RNA detection in plasma specimens, and western blot assay are the mainstay of clinical diagnosis (15), in several studies on HIVexposed seronegative individuals (HESN) proviral DNA of HIV-1 has been diagnosed in PBMC samples using polymerase chain reaction (PCR). The seronegative infection has been reported in health care personnel accidentally exposed to infected blood, in people who have frequent blood transfusions, sexual partners of HIV-infected people, and also in children of HIV-1 positive mothers (1,16).…”
Section: Introductionmentioning
confidence: 99%